Who Killed the Winograd Schema Challenge? - Neri, Hugo; Cozman, Fabio G. (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2023: Anais da XII Brazilian Conference on Intelligent Systems, 2023)
In which we investigate the technical issues surrounding the defeat, or perhaps the sudden assassination, of the Winograd Schema Challenge. We argue that, while the obvious suspect is the WinoGrande-based solution, the real cause of death was the masked language modeling technique for learning large language models. The Winograd Schema Challenge was, in the end, just a test for masked language closure, and as such it was killed by the use of this technique at scale.